IMPLEMENTASI HOTS PADA PEMBELAJARAN MATEMATIKA SD/MI KELAS 6 - Fuaddilah Ali Sofyan; Agela Ingries Fihtanti (Universitas Negeri Medan, 2019)
Abstract: Implementation of HOTS in Mathematics Learning for Elementary School / MI Class 6. This study aims to describe the implementation of learning based on High Order Thinking Skills (HOTS) in SD N 29 Palembang schools. What we already know in the 2013 curriculum requires that to implement HOTS-based learning because HOTS learning is very important for students, especially elementary school children. The lack of ability to think at a higher level is therefore to continue to be trained and honed so that they have the ability to think at a high level, especially for grade 6 children. This research is a descriptive study with a qualitative approach. and data collected with interview guidelines, observation sheets, and documentation. The results showed that the success rate of teachers in formulating HOTS-based learning planning was good enough and in the implementation of HOTS-based learning had been implemented and the categories were sufficient, and the success rate in the formulation of authentic HOTS-based assessments was also in the sufficient category. Thus it is still in the stage of improvement in the implementation of HOTS-based authentic learning and assessment in SD N 25 Palembang.Keywords: HOTS, LearnersAbstrak: Implementasi HOTS pada Pembelajaran Matematika SD/MI Kelas 6. Penelitian ini bertujuan untuk mendeskripsikan implementasi pembelajaran berbasis High Order Thinking Skills (HOTS) di sekolah SDN 25 Palembang. Yang mana telah kita ketahui pada kurikulum 2013 itu mewajibkan untuk menerapkan pembelajaran berbasis HOTS karena pembelajaran HOTS ini sangatlah penting untuk peserta didik terutama anak SD. Kurangnya kemampuan dalam berpikir tingkat tinggi maka dari itu untuk terus dilatih dan diasah agar memiliki kemampuan berpikir tingkat tinggi terkhusus untuk peserta didik kelas 6 sekolah dasar. penelitian ini merupakan penelitian deskriptif dengan pendekatan kualitatif. dan data dikumpulkan dengan pedoman wawancara, lembar observasi, dan dokumentasi. Hasil penelitian menunjukan bahwa tingkat keberhasilan guru dalam merumuskan perencanaan pembelajaran berbasis HOTS sudah baik dan dalam pelaksaan pembelajaran berbasis HOTS sudah terlaksana dan katagori cukup baik, serta tingkat keberhasilan dalam perumusan penilaian autentik berbasis HOTS juga berada dalam kategori cukup. Dengan demikian masih dalam tahap perbaikan dalam pelaksanaan pembelajaran dan penilaian autentik berbasis HOTS di SD N 25 Palembang.Kata Kunci: HOTS, Peserta Didik.